PENERAPAN PEMBELAJARAN DISCOVERY LEARNING UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR IPA PADA MATERI GAYA DAN HUKUM NEWTON TERHADAP PESERTA DIDIK KELAS VIII-1 SMP NEGERI 2 SOPPENG RIAJA KABUPATEN BARRU - Muhammad Tang (Universtas Negeri Makassar, 2021)
This classroom action research was conducted to improve science learning problems in class VIII-1, namely the low learning outcomes. This research was carried out in 2 cycles where the subjects in the study were 25 students of class VIII-1 SMP Negeri 2 Soppeng Riaja in the Even Semester of the 2019/2020 Academic Year. In each cycle, observations were made on the implementation of Discovery Learning learning through observation sheets at each meeting and learning motivation which was assessed based on a learning motivation questionnaire. This study aims to: (1) determine the learning motivation of class VIII-1 students who are taught by the Discovery Learning learning model. (2) knowing the learning outcomes of class VIII-1 students who were taught with the Discovery Learning learning model on the force and Newton's Laws. The indicator of research success is that learning outcomes increase and meet the minimum completeness criteria and learning motivation meets 88% achievement. Actions taken to improve and increase motivation and science learning outcomes by: (1) motivating and stimulating students in stimulation activities and problem identification, especially in formulating hypotheses in Discovery Learning learning (2) intensifying guidance for groups experiencing difficulties in learning, (3 ) grouping by rearranging the location of each group in the class, (4) directing each group member who has understood the subject matter to be more active in guiding group members who have difficulty in learning, (5) more stimulating or encouraging active participation of students in learning. prove the hypothesis based on the results of data collection, (6) conduct a review and/or reinforcement as well as provide an award or reward. a student of class VIII-1 of SMP Negeri 2 Soppeng Riaja, Barru Regency.